Polysilicon nanogap fabrication using a thermal oxidation process - Dhahi, T.S; Uda, Hashim, Prof. Dr.; Md. Eaqub, Ali; Nazwa, Taib (Emerald Group Publishing Limited., 2013)
Link to publisher's homepage at http://www.emeraldinsight.com/